2023
DOI: 10.3389/fnagi.2023.1087749
|View full text |Cite
|
Sign up to set email alerts
|

Opposite pattern of transcranial direct current stimulation effects in middle-aged and older adults: Behavioral and neurophysiological evidence

Abstract: IntroductionEpisodic memory (EM) exhibits an age-related decline, with overall increased impairment after the age of 65. The application of transcranial direct current stimulation (tDCS) to ameliorate cognitive decline in ageing has been extensively investigated, but its efficacy has been reported with mixed results. In this study, we aimed to assess whether age contributes to interindividual variability in tDCS efficacy.MethodsThirty-eight healthy adults between 50 and 81 years old received anodal tDCS over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…A recent study reported contrary effects of anodal tDCS in middle aged (50–64 years) and older (65–81 years) adults. While older adults showed better recognition performance after stimulation over the left dorsolateral prefrontal cortex (DLPFC) during encoding, middle aged adults performed worse ( Bagattini et al, 2023 ). Computerized cognitive training (CCT) of working memory and concurrent stimulation moreover benefitted older adults more than young adults ( Pergher et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported contrary effects of anodal tDCS in middle aged (50–64 years) and older (65–81 years) adults. While older adults showed better recognition performance after stimulation over the left dorsolateral prefrontal cortex (DLPFC) during encoding, middle aged adults performed worse ( Bagattini et al, 2023 ). Computerized cognitive training (CCT) of working memory and concurrent stimulation moreover benefitted older adults more than young adults ( Pergher et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%